Anti‐aging and filling efficacy of six types hyaluronic acid based dermo‐cosmetic treatment: double blind, randomized clinical trial of efficacy and safety. (December 2014) - Nobile, Vincenzo; Buonocore, Daniela; Michelotti, Angela; Marzatico, Fulvio
Summary Background Human skin aging is a multifactorial and complex biological process affecting the different skin constituents. Even if the skin aging mechanism is not yet fully unravelled is evident that epidermis loses the principal molecule responsible for binding and retaining water molecules, resulting in loss of skin moisture and accounting for some of the most striking alterations of the aged skin. Objectives This Study investigated the cosmetic filling efficacy of Fillerina® in decreasing the skin aging signs and in improving facial volume deficiencies. Methods A placebo‐controlled, double‐blind, randomized clinical trial was carried out on 40 healthy female subjects showing mild to moderate clinical signs of skin aging. The effect of the treatment on skin surface and on face volumes was assessed both in the short‐term (3 h after a single product application) and in the long‐term (7, 14, and 30 days after continuative daily use). Results Three hours after a single application and after 7, 14, and 30 days of treatment the lips volume was increased by 8.5%, 11.3%, 12.8%, and 14.2%. After 7, 14, and 30 days: (1) skin sagging of the face contours was decreased by −0.443 ± 0.286, −1.124 ± 0.511, and −1.326 ± 0.649 mm, respectively; (2) skin sagging of the cheekbones contours was decreased by −0.989 ± 0.585, −2.500 ± 0.929, and −2.517 ± 0.927 mm, respectively; (3) cheekbones volume was increased by 0.875 ± 0.519, 2.186 ± 0.781, and 2.275 ± 0.725 mm, respectively; (4) wrinkle volume was decreased by −11.3%, −18.4%, and −26.3%, respectively; and (5) wrinkle depth was decreased by −8.4%, −14.5%, and −21.8% respectively. Conclusion This study demonstrated the positive filling effect of Fillerina® in decreasing the clinical signs of skin aging and in improving the face volumes.